2008
DOI: 10.1002/jor.20629
|View full text |Cite
|
Sign up to set email alerts
|

Changes of selenium, copper, and zinc content in hair and serum of patients with idiopathic scoliosis

Abstract: Our work aimed at extending the search for abnormalities of trace elements in patients with idiopathic scoliosis to the content of zinc (Zn), copper (Cu), and selenium (Se) in these subject's hair and serum. A total of 59 patients (54 girls and 4 boys) with idiopathic scoliosis, aged 13 on the average (range, 10-18 years), were examined. The degree of spine curvature deformity ranged between 128 and 828. The hair of scoliotic patients under examination showed significantly increased content of zinc 263 AE 108 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…In some studies, serum selenium levels were found to be low in the scoliosis patients [10,13,14]. In a study for example, selenium levels both in the serum and in hair samples were found to be low in IS patients [14].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In some studies, serum selenium levels were found to be low in the scoliosis patients [10,13,14]. In a study for example, selenium levels both in the serum and in hair samples were found to be low in IS patients [14].…”
Section: Discussionmentioning
confidence: 96%
“…In a study for example, selenium levels both in the serum and in hair samples were found to be low in IS patients [14]. Dastych et al compared vertebra curvature levels with serum selenium, zinc, and copper levels in their study and found that patients with more than 45° curvature who required surgical treatment had significantly lower levels of serum selenium and serum/albumin ratio compared to patients with less than 45° curvature [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the exact mechanism how copper-chelating agents induce scoliosis is unclear. Previous studies had shown that the hair copper concentration was significantly higher in patients with scoliosis versus control group [14]. The potential mechanisms in the pathogenesis of congenital scoliosis of WD included genetic variant and excessive accumulation of copper during pregnancy.…”
Section: Case Presentationmentioning
confidence: 99%